Case report: Cerebellar Tuberculoma Mimicking Malignant Tumor - ลอยเมฆ ธนพงษ์; บุณยะรัตเวช กฤษณพันธ์ (Thai Journal of Neurological Surgery, 2025)
This is a 23-year-old female presented with headache due to increased intracranial pressure and cerebellar dysfunction. The radiographic study showed a ring enhancing mass at the left cerebellar hemi- sphere. The patient underwent median suboccipital craniectomy and removal of the mass. Pathological examination revealed tuberculoma which is rare at this location and its radiographic findings often mimick those of other malignant tumors. The authors also reviewed the literature of intracranial tuberculoma in the aspects which are related to this case.